Prospects for greater competition amongst European Community airlines - C. J. Redston (Intereconomics, 1985)
The deregulation of civil aviation in the United States has led to customers being offered a wider choice of flights at lower fares, whereas deregulation within the european Community is still a distant prospect. Chris Redston examines the proposals of the European Commission for liberalization and assesses their chances of success.
Keywords: 330